From the use of space to territorialisation during the Early Holocene in Taltal, coastal Atacama Desert, Chile - Salazar, Diego; Arenas, Camila; Andrade, Pedro; Olguin, Laura; Torres Elgueta, Jimena Andrea; Flores, Carola; Vargas, Gabriel; Rebolledo, Sandra; Borie, Cesar; Sandoval, Consuelo; Silva, Claudia; Delgado, Ayelen; et al. (My University, 2018)
In this paper, we present recent data on Early Holocene human occupations from Taltal, in the coast of the Atacama Desert. We focus on evidences of mobility and subsistence economy, discussing the data in terms of a concept of territoriality adapted from cultural geographers working with hunting-gathering societies. We attempt to show that the Huentelauquen Cultural Complex, usually considered the earliest evidence of human occupation in the coast of northern Chile, exhibits an already consolidated territorialisation process. We question whether it represents the earliest phases of the peopling process or if such evidence are still lacking at a regional level. We try to go beyond the characterization of Huentelauquen Cultural Complex as an early maritime adaptation, understanding it as the earliest socioterritorial identity known to date for the Arid Coast of northern Chile. (C) 2017 Elsevier Ltd and INQUA. All rights reserved.
Keywords: coastal northern chile; early holocene; huentelauquen cultural complex; territorialisation